Core Area Housing Redevelopment in sub-Sahara Africa: Example of Ile-Ife, Nigeria - Adewale Yoade; S A Olatunji (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2022)
In most nations of the third world, the large proportion of the cities are plagued with different multi dimmentional urban growth challenges. The problem of the central city slum and the required solution has some socioeconomic, technical, administrative and socio-cultural considerations. It is in this regard that this paper has attempted an examination of the housing redevelopment in Ile-Ife, Nigeria. Data for this study were derived through the use of questionnaire administered on 476 houses samples of household heass selected using systematic random sampling. Both descriptive and inferential statistics were utilized for this study. Findings established that the majority of the buildings was built more than 30 years ago in the study area. Also, the study revealed that most of the respondents earned less than #15,000 (less than 30) monthly while only few earned more than #15,000. The paper concluded that in urban renewal endeavors, there is need for planners to take into consideration the various socioeconomic and socio-cultural encumbrances if affected people will be meaningfully catered for.